Identification of the dependences between liquidity risk and internal determinants in Polish banks - Wójcik-Mazur, Agnieszka (Identyfikacja relacji pomiędzy ryzykiem płynności a determinantami wewnętrznymi w polskich bankach, 2019)
This article assesses the correlation between the level of liquidity risk of banks operating in the Polish banking system and a group of internal determinants (including credit risk, measure of profitability and the value of capital ratio). The estimation of correlation coefficients was performed in a group of two types of banks representing the Polish banking sector i.e. commercial and cooperative banks. The study showed a correlation (statistically significant) between the level of liquidity and the internal determinants in the two groups of banks. Nevertheless, the existence of different directions of correlation between liquidity risk and the level of capital ratio in these two groups of Polish banks has been demonstrated. A strong positive relation between the level of liquidity and capital ratio has been diagnosed in the cooperative banking sector, which may be interpreted as an orientation of these banks to increase financial security, regardless of the phase of the economic cycle, which results from both the necessity to implement CRD regulation and the increase in the lending capability of cooperative banks
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 2, s. 130-142
Keywords: bank; liquidity risk; determinants of liquidity risk; ryzyko płynności; determinanty ryzyka płynności